Socioeconomic differences in children's and adolescents' hospital admissions in Germany: a report based on health insurance data on selected diagnostic categories. Issue 2 (1st February 2002) - Geyer, S; Peter, R; Siegrist, J
Abstract : Study objective: The extent of social inequalities in children's hospitalisation risks was examined in terms of socioeconomic status and parents' nationality. This was considered in terms of inpatient treatment attributable to a number of diagnoses (ICD-9), especially infectious diseases and psychiatric disorders. Design and setting: Analyses were performed with records of a German statutory health insurance comprising 48 412 (52.8% male and 47.2% female) children and adolescents of 15 years of age or younger who were co-insured between 1987 and 1996. Classification of socioeconomic position was based on parental occupational position. Results: Social inequalities in terms of hospital admissions attributable to acute diseases were rather small. The only exception were infections of the respiratory organs: in the highest status positions as compared with the lowest one the relative risk for being admitted was RR=0.22 (95% CI 0.06 to 0.89). However, length of stay in hospital was significantly related to socioeconomic position for infections of the upper respiratory tract and infections of the respiratory organs, with children and adolescents with the lowest socioeconomic background having spent the longest periods in hospital. With regard to nationality, pneumonia/flu was the only diagnostic category where relative risks for being admitted were higher in non-German children and adolescents (RR=1.5; 95% CI 1.2 to 1.8). Conversely, hospital admissions attributable to psychiatric diagnoses were significantly lower among non-German patients (RR=0.43; 95% CI 0.30 to 0.61), thus suggesting differential utilisation patterns according to nationality. Conclusions: Health inequalities in children's and adolescents' hospital admissions in Germany are small and inconsistent if parents' socioeconomic status and nationality are taken as criterion. Yet, children of lower status background stay longer in hospital if suffering from highly prevalent infectious diseases. This last observation may be attributable to more severe disease conditions.